2012
DOI: 10.1121/1.4757730
|View full text |Cite
|
Sign up to set email alerts
|

English sentence recognition in speech-shaped noise and multi-talker babble for English-, Chinese-, and Korean-native listeners

Abstract: This study aimed to investigate English sentence recognition in quiet and two types of maskers, multi-talker babble (MTB) and long-term speech-shaped noise (LTSSN), with varied signal-to-noise ratios, for English-, Chinese-, and Korean-native listeners. Results showed that first, sentence recognition for non-native listeners was affected more by background noise than that for native listeners; second, the masking effects of LTSSN were similar between Chinese and Korean listeners, but the masking effects of MTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
1
23
2
Order By: Relevance
“…Different from previous studies (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012;Jin and Liu, 2014), we found a significant difference between CN L1 and L2 perception with only with interfering babble, not with SSN. Consistent with previous studies (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012), the difference in performance between L1 and L2 was greater for babble than for SSN. Interestingly, a slight release from masking (babble DRT -SSN DRT) was only observed for L1 in CN subjects; L1 performance with babble slightly worsened for EN subjects, relative to SSN.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Different from previous studies (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012;Jin and Liu, 2014), we found a significant difference between CN L1 and L2 perception with only with interfering babble, not with SSN. Consistent with previous studies (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012), the difference in performance between L1 and L2 was greater for babble than for SSN. Interestingly, a slight release from masking (babble DRT -SSN DRT) was only observed for L1 in CN subjects; L1 performance with babble slightly worsened for EN subjects, relative to SSN.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, non-native listeners in the "real" world must overcome both "imperfect" signals and knowledge of L2. Under adverse listening conditions, L2 listeners are more susceptible to interfering noise than are L1 listeners, regardless of speech stimulus type (phoneme, word, or sentence) (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012). Noise can interfere with speech by overlapping the target speech spectrum ("energetic masking") and/or by presenting temporal information that is similar to the target temporal envelope ("informational masking").…”
Section: Introductionmentioning
confidence: 99%
“…This native advantage in speech perception was found across a wide variety of types of noise such as long-term speech-shaped noise (LTSSN) and babble, [1][2][3][4][5] depending on the number of cues that are available to listeners in speech tasks 3 (for a review, see Garcia Lecumberri et al 6 ). Compared with steady noise like LTSSN, multi-talker babble (MTB) is an amplitude-modulating noise in which listeners may take advantage of momentary dips, resulting in better speech perception in MTB than in LTSSN.…”
Section: Introductionmentioning
confidence: 97%
“…This difference in masking release between native and non-native listeners could be due to the difference in the efficiency of using acousticphonetic cues in temporal dips of the MTB and/or the different use of suprasegmental cues among listeners with different language backgrounds. 4 Although these studies measured sentence recognition and consonant identification in noise, few data have been reported on vowel identification in noise for native and non-native listeners. The primary goal of this study was to investigate the effects of two types of noise, LTSSN and MTB, on vowel identification by English-and Chinese-native listeners, in which there were only acoustic-phonetic cues available (i.e., no suprasegmental cues).…”
Section: Introductionmentioning
confidence: 99%
“…Since, it is well-established that the effect of noise on such cognitive tasks is greater for speakers for whom the language used in the task is not their native language, but a second language (i.e. non-native English speakers), [22,23] both native English speakers as well as non-native English speakers were in the study sample.…”
Section: Introductionmentioning
confidence: 99%